2013
DOI: 10.3892/etm.2013.1455
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin levels in nondipper and dipper hypertensive patients

Abstract: A number of studies have focused on the association between sphingomyelin (SM) levels and atherosclerosis, however, there are few data concerning the correlation of SM with nondipper hypertension. The present study aimed to investigate the correlation between plasma SM levels and nondipper status in patients with hypertension. A total of 200 hypertensive patients were enrolled and divided into two groups according to their ambulatory blood pressure monitoring (AMBP) results: Dipper group (84 patients) and nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Here, we summarized a randomized controlled study and meta-analysis on the drug treatment of left ventricular hypertrophy (LVH) or cardiac remodeling from 2013–2023 (Table 1 , Ref. [ 22 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ]). However, even with medical treatment, patients with HHD still face the risk of progressing to heart failure (HFpEF or HFrEF) and SCD, and the use of antihypertensive drugs is ineffective in reducing the risk of sudden death in hypertensive patients (relative risk (RR): 0.96, 95% confidence interval (95% CI): 0.81–1.15) [ 16 , 214 , 215 ].…”
Section: Potential Treatments For Hhdmentioning
confidence: 99%
“…Here, we summarized a randomized controlled study and meta-analysis on the drug treatment of left ventricular hypertrophy (LVH) or cardiac remodeling from 2013–2023 (Table 1 , Ref. [ 22 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 ]). However, even with medical treatment, patients with HHD still face the risk of progressing to heart failure (HFpEF or HFrEF) and SCD, and the use of antihypertensive drugs is ineffective in reducing the risk of sudden death in hypertensive patients (relative risk (RR): 0.96, 95% confidence interval (95% CI): 0.81–1.15) [ 16 , 214 , 215 ].…”
Section: Potential Treatments For Hhdmentioning
confidence: 99%
“…Moreover, it has been shown that plasma concentrations of S1P were significantly correlated with impaired endothelial function assessed by the Reactive Hyperemia index and a higher aortic systolic pressure ( 34 ). In addition, Zheng et al showed that plasma SM concentrations in patients with hypertension but without a physiological nocturnal reduction of ≥10% of blood pressure (non-dippers) was significantly higher in comparison with the dipper group and plasma SM levels were negatively correlated with the degree of systolic and diastolic blood pressure decrease at night ( 45 ).…”
Section: Sphingolipids In Cardiovascular Diseasesmentioning
confidence: 99%